PRODUCTION SYSTEM IMPROVEMENT THROUGH KANBAN APPLICATION IN LABOR INTENSIVE COMPANY - Novera Elisa Triana; Meike Elsye Beatrix (Universitas Mercu Buana, 2019)
Delivery performance is essential for a manufacturer to meet customer requirement. The only manufacturer with fast, accurate and on time delivery could survive in global competition as a sports shoe manufacturer with the labor-intensive production process, PT. XYZ faced a problem with massive work in process inventory that impacted low delivery performance. This research aims to support the shoe manufacturer company to reduce work in process inventory by applying Kanban System. The manufacturer company can decrease work in process in the production line and cut the lead time of production. Kanban System can be utilized from receiving material process, production process, until the packaging process. By implementing a kanban system correctly and consistently, the company can control material supply, production material usage, and customer order delivery inaccurate process. With controlled those items, the company could monitor and manage material and process from beginning to end of the process, even to monitor distribution to a customer. The result of analysis proves that by applying kanban system can achieve the specified daily production target without work in process inventory.